P161 Adopting a political economy approach to HIV research: a case study of ongoing conflict in ukraine. (14th July 2019) - Herpai, Nicole; Becker, Marissa; Balakireva, Olga; Pavlova, Daryna; Cheuk, Eve; Lorway, Robert; Pickles, Michael; Aral, Sevgi; Mishra, Sharmistha; Blanchard, James; Forget, Evelyn
Abstract : Background: Armed conflict erupted in eastern Ukraine in 2014. Ukraine has the highest HIV rates in Europe, there is concern that the epidemic can worsen in the current climate. Past research on HIV prevalence in conflict zones has been limited and the few studies that exist yield contradictory results. In this paper we describe the historical events leading up to the current conflict and explore its politico-socio-economic consequences as related to HIV risk. Methods: This project takes a political economy approach to examine Ukraine as a case study to understand the impact of conflict on HIV and HCV. We undertook archival research to examine the structural factors related to the current conflict and its politico-socio-economic consequences. Political economy draws upon economic, political, historical, cultural and sociological approaches to examine the evolution of states, markets and society. This perspective accounts for a wide range of factors that influence the downstream realities of people living with HIV. It illuminates the structural parameters of conflict within which the epidemics exists. Results: Preliminary results reveal that the social, political, and economic turmoil leading up to the armed conflict can be traced back to Ukraine's formation as a sovereign state following the dissolution of the Soviet Union. These factors have also been associated with the beginning of Ukraine's HIV epidemic. High inflation, deep recessions, and a bourgeoning kleoptocracy led to civil unrest and the ousting of the president which was followed by backlash from Russia. The ensuing conflict has ignited several factors known to contribute to HIV risk such as violence, migration and increased mobilization of armed forces might be expected to exacerbate prevalence. Conclusion: Ukraine as a case study presents a unique opportunity to examine the influences of conflict on the HIV epidemic before, during and possibly post conflict. Disclosure: No significant relationships.